Naples Prognostic Score, Based on Nutritional and Inflammatory Status, is an Independent Predictor of Long-term Outcome in Patients Undergoing Surgery for Colorectal Cancer. Issue 12 (December 2017) - Galizia, Gennaro; Lieto, Eva; Auricchio, Annamaria; Cardella, Francesca; Mabilia, Andrea; Podzemny, Vlasta; Castellano, Paolo; Orditura, Michele; Napolitano, Vincenzo
Abstract : BACKGROUND: The existing scores reflecting the patient's nutritional and inflammatory status do not include all biomarkers and have been poorly studied in colorectal cancers. OBJECTIVE: The purpose of this study was to assess a new prognostic tool, the Naples prognostic score, comparing it with the prognostic nutritional index, controlling nutritional status score, and systemic inflammation score. DESIGN: This was an analysis of patients undergoing surgery for colorectal cancer. SETTINGS: The study was conducted at a university hospital. PATIENTS: A total of 562 patients who underwent surgery for colorectal cancer in July 2004 through June 2014 and 468 patients undergoing potentially curative surgery were included. MaxStat analysis dichotomized neutrophil:lymphocyte ratio, lymphocyte:monocyte ratio, prognostic nutritional index, and the controlling nutritional status score. The Naples prognostic scores were divided into 3 groups (group 0, 1, and 2). The receiver operating characteristic curve for censored survival data compared the prognostic performance of the scoring systems. MAIN OUTCOME MEASURES: Overall survival and complication rates in all patients, as well as recurrence and disease-free survival rates in radically resected patients, were measured. RESULTS: The Naples prognostic score correlated positively with the other scoring systems ( p < 0.001) and worsened with advanced tumor stages ( p < 0.001). Patients with the worst Naples prognostic score experienced more postoperative complications (all patients, p = 0.010; radically resected patients, p = 0.026). Compared with group 0, patients in groups 1 and 2 had worse overall (group 1, HR = 2.90; group 2, HR = 8.01; p < 0.001) and disease-free survival rates (group 1, HR = 2.57; group 2, HR = 6.95; p < 0.001). Only the Naples prognostic score was an independent significant predictor of overall (HR = 2.0; p = 0.03) and disease-free survival rates (HR = 2.6; p = 0.01). The receiver operating characteristic curve analysis showed that the Naples prognostic score had the best prognostic performance and discriminatory power for overall ( p = 0.02) and disease-free survival ( p = 0.04). LIMITATIONS: This is a single-center study, and its validity needs additional external validation. CONCLUSIONS: The Naples prognostic score is a simple tool strongly associated with long-term outcome in patients undergoing surgery for colorectal cancer. SeeVideo Abstract athttp://links.lww.com/DCR/A469 . Abstract : Supplemental Digital Content is available in the text.